Comparison of the Financial Performance between Square Pharmaceuticals Limited and Beximco Pharmaceuticals Limited: DuPont Analysis - Ahamed, Mohammad Jafaur (Global Disclosure of Economics and Business, 2020)
The study attempts to make a comparison of financial strength between Square Pharmaceuticals Limited (SQPL) and Beximco Pharmaceuticals Limited (BXPL) by using the technique of DuPont analysis. Pharmaceuticals are selected here based on a purposive sampling method with the criteria of convenience in annual reports availability. The research is based on secondary data available in annual reports of FY 2018-19 of the selected companies. The study reveals that in comparison with BXPL, SQPL has been utilizing its owners’ funds more profitably, doing operational activities more efficiently, and earning enough returns for its owners. Beximco Pharmaceuticals Ltd. applies aggressive debt-equity policy, which does not magnify its earnings due to the lack of its sufficient rate of returns in comparison with interest burden, lack of core operational efficiency, and underutilization of resources. At the same time, leverage helps the SQPL to fuel the growth of the business. There is a good thing that the two companies have almost the same amount of tax burden ratio, although EBIT is highly differing between the companies. The study suggests that to achieve a high RoE, Beximco Pharmaceuticals Company must reduce its interest expenses, utilize its full capacities, and increase its assets turnover. Besides, both the pharmaceuticals are suggested to focus on the inflation-adjusted financial items in its annual reports. The study has operated only on DuPont analysis. Thus further research is recommended to conduct focusing on others such as common-size analysis, comparative analysis, trend analysis, and ratio analysis, etc. to investigate the financial health of pharmaceutical companies.